Basin-wide distribution of phytoplankton lipids in the South China Sea during intermonsoon seasons: Influence by nutrient and physical dynamics. (December 2015) - Dong, Liang; Li, Li; Li, Qianyu; Liu, Jie; Chen, Yuxing; He, Juan; Wang, Hui
Abstract: Four algal biomarkers, brassicasterol, C30 -diol/keto-ol, dinosterol and C37 -alkenone, representing diatoms, estigmatophytes, dinoflagellates and coccolithophorids, respectively, were detected in samples collected during two South China Sea cruises to study the modern phytoplankton community structure in the region. For the first time, the basin-wide distribution of these phytoplankton algal biomarkers in the sea surface water during two intermonsoon seasons (spring 2010 and autumn 2011) is documented and charted. Generally, the abundance of the biomass is higher in spring than autumn, with high productivity mostly in the regions of Pearl River estuary, off Palawan and around the Luzon Strait, showing the abundance order: diatoms>estigmatophytes>dinoflagellates>coccolithophorids. We run both redundancy analysis (RDA) and SPSS correlation analysis to interpret the relationship between individual groups and environmental variables. The results indicate that temperature and salinity play a dominant role in controlling the distribution of phytoplankton in these intermonsoon seasons, followed by nitrate playing a secondary role. Our biomarker survey provides important reference data for interpreting paleo-productivity in the geological records in the SCS.